Respostas
respondido por:
3
10 - 4y = y
10 - 4y - y = 0
10 - 5y = 0
10 = 5y
y = 10 / 5
y = 2
Espero ter ajudado. Valeu!
10 - 4y - y = 0
10 - 5y = 0
10 = 5y
y = 10 / 5
y = 2
Espero ter ajudado. Valeu!
pablosilveira01023:
Cara valeu viu
respondido por:
3
10 - 4y = y
-4y - y = -10
-5y = -10
y = -10/-5
y = 2
Espero ter ajudado, bons estudos. Abraços
-4y - y = -10
-5y = -10
y = -10/-5
y = 2
Espero ter ajudado, bons estudos. Abraços
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás